Inhibition of UBE2L6 attenuates ISGylation and impedes ATRA‐induced differentiation of leukemic cells - Nina Orfali; Deborah Shan‐Krauer; Tracey R. O’Donovan; Nigel P. Mongan; Lorraine J. Gudas; Mary R. Cahill; Mario P. Tschan; Sharon L. McKenna (Molecular Oncology, 2020)
Ubiquitin/ISG15‐conjugating enzyme E2L6 (UBE2L6) is a critical enzyme in ISGylation, a post‐translational protein modification that conjugates the ubiquitin‐like modifier, interferon‐stimulated gene 15 (ISG15), to target substrates. Previous gene expression studies in acute promyelocytic leukemia (APL) cells showed that all‐trans‐retinoic acid (ATRA) altered the expression of many genes, including UBE2L6 (200‐fold) and other members of the ISGylation pathway. Through gene expression analyses in a cohort of 98 acute myeloid leukemia (AML) patient samples and in primary neutrophils from healthy donors, we found that UBE2L6 gene expression is reduced in primary AML cells compared with normal mature granulocytes. To assess whether UBE2L6 expression is important for leukemic cell differentiation—two cell line models were employed: the human APL cell line NB4 and its ATRA‐resistant NB4R counterpart, as well as the ATRA‐sensitive human AML HL60 cells along with their ATRA‐resistant subclone—HL60R. ATRA strongly induced UBE2L6 in NB4 APL cells and in ATRA‐sensitive HL60 AML cells, but not in the ATRA‐resistant NB4R and HL60R cells. Furthermore, short hairpin (sh)RNA‐mediated UBE2L6 depletion in NB4 cells impeded ATRA‐mediated differentiation, suggesting a functional role for UBE2L6 in leukemic cell differentiation. In addition, ATRA induced ISG15 gene expression in NB4 APL cells, leading to increased levels of both free ISG15 protein and ISG15 conjugates. UBE2L6 depletion attenuated ATRA‐induced ISG15 conjugation. Knockdown of ISG15 in NB4 APL cells inhibited ISGylation and also attenuated ATRA‐induced differentiation. In summary, we demonstrate the functional importance of UBE2L6 in ATRA‐induced neutrophil differentiation of APL cells and propose that this may be mediated by its catalytic role in ISGylation.